PENGARUH INFLASI, NILAI TUKAR RUPIAH, SUKU BUNGA PASAR UANG DOMESTIK DAN SUKU BUNGA PASAR UANG LUAR NEGERI TERHADAP YIELD TO MATURITY OBLIGASI RITEL INDONESIA DI BURSA ANTAR BANK PERIODE 2010-2013 - Andri Lambas Lumbantobing (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract.This paper has an aim to know the effect of inflation, exchange rate of IDR, the interest rate of JIBOR, and SIBOR toward yield to maturity of Indonesia Ritel Bond (ORI). The research result of 37 sample with population of ten kind of Indonesia Ritel Bond (ORI) those are ORI001 to ORI010 can be concluded that inflation, exchange rate of IDR, the interest rate of JIBOR, and SIBOR have simultaniously influenced toward yield to maturity of Indonesia Ritel Bond (ORI). However especially for Interest rate of SIBOR, it has an individually influenced toward yield to maturity of Indonesia Ritel Bond (ORI). The test model result shows that 0,712 % adjusted R Square. It means that inflation, exchange rate of IDR, the interest rate of JIBOR, and SIBOR influence 71% toward yield to maturity of Indonesia Ritel Bond (ORI) and the other 29% effect is fromother factors. The thing that make this research is interesting is that independent variable can only simustaniously influenced toward YTM of Indonesia Ritel Bond (ORI), except the interest rate of SIBOR, from spss coefficients result shows that it individually influance toward yield to maturity of Indonesia Ritel Bond (ORI).Key words : Yield to maturity, Indonesia Ritel Bond (ORI), inflation, exchange rate of IDR, theinterest rate of JIBOR, and SIBOR .